Epidemiological characterization of glaucoma Service population Ophthalmology Archbishop Loayza National Hospital: January to december 2012 - Zárate Ferro, Úrsula Erika (2013)
Purpose: To describe clinical and epidemiological characteristics of glaucoma patients evaluated by medical faculty of Glaucoma Unit at ArzobispoLoayza Hospital`s Ophthalmology Department since January through December 2012. Material and methods: Descriptive, retrospective and observational study of 190 medical charts of patients evaluated at Glaucoma Unit of ArzobispoLoayza Hospital since January through December 2012. The collected data were converted to Microsoft Excel program and transferred to SPSS v 21.0 for statistical analysis. Results: Of 190 patients, 130 patients were diagnosed of glaucoma: 88 women (66.7 %) and 42 males (32.3 %) with mean age of 60.18 years. Most of the cases were classified as primary open angle glaucoma (POAG  corresponding to 50 % of the subtypes found (n=65), followed by glaucoma suspects (n=25, 19.23%), primary angleclosure glaucoma (PACG), (n=20, 15.4%), ocular hypertension (OHT), (n=17, 13.1%), normal tension glaucoma (NTG), (n=2, 1.5%), and neovascular glaucoma (NVG), (n=1, 0.8%). Conclusions: The most common form of glaucoma was POAG and the mean age was 64 years. It was found that the number of cases of POAG and PACG increased twofold in patients over 60 years old.